Parenting skills affect child behaviors in a selected area of Nepal - Hossain, Sarder Mahmud; Huq, Sazia; Adhikari, Biswas; Eusuf Zai, Sumaiya Zabin; Haque, Syed Mohammad Tanjilul (South East Asia Journal of Public Health, 2015)
Acting out, or misbehavior, is often associated with ineffective parenting. It negatively affects children across socio-economic backgrounds. While ineffective parenting might not solely be the blame for negative behaviors in children, parenting contributes significantly to children's behavioral outcomes. Till now there is lack of data regarding child behavior affected by parenting skill in Nepal. The aim of the study was to assess the effects of parenting skill on children behavior. In this descriptive type of cross-sectional study 369 respondents were selected by purposive sampling in some selected areas of Nepal. The mean age of the respondents was 36.14±6.69 years with 92.7% female and of them 92.1% were married. Out of 184 respondents, 45.1% gave proper childcare/love/sufficient time to children. Among the respondents 68% had spent quality time with their children very frequently. Statistically an association was found between parenting skill (quality time with children) and different behavior of children. Rearing children always needs good parenting skills which help to change the future of the nation by pro-ducing skilled, well behaved, intelligent citizens in the days to come. As such awareness about parenting skill should be made generalized and easily accessible to all eligible couples in the country. South East Asia Journal of Public Health Vol.5(1) 2015: 44-48